Leader-expressed humility predicting team psychological safety: A personality dynamics lens - Rego, A.; Melo, A. I.; Bluhm, D. J.; Cunha, M. P. e.; Júnior, D. R. (Journal of Business Ethics, 2021)
In an application of the personality dynamics framework, we advance understanding on the relationship between baseline leader humility and team psychological safety by exploring the roles of humility variability and attractor strength. Specifically, we examine how the (in)consistency (i.e., variability) of leader-expressed humility across team members operates as a boundary condition in the relationship between leader-expressed humility and team psychological safety. We also explore how the agreement between leader self-reported humility and leader-expressed humility (i.e., self-other agreement, SOA) operates as an attractor to predict such a consistency. We test the hypothesized model through a sample of 85 teams, rated by 354 team members. The findings suggest that consistency reinforces, while inconsistency weakens, the effect of leader-expressed humility on team psychological safety. The findings also reveal that SOA relates to the consistency of leader-expressed humility, depending on the level at which the (dis)agreement occurs. We conclude that to better understand the outcomes of humble leadership, it is necessary to take into account not only the baseline of humility expressed by the leader (as most studies do), but also his/her humility variability and the strength of the attractor.